Examination of Simple Outcome Measures and Cut-off Values Related to Walking Independence of Inpatients with Medical Diseases in Acute Care Hospitals - Yamauchi, Shinya (Prog Rehabil Med, 2017)
OBJECTIVE: The objective of the current study was to identify simple outcome measures to predict walking independence in inpatients with medical diseases in acute care hospitals and to identify the cut-off values of the relevant measures. METHODS: Two hundred inpatients aged 20 years or above who had a medical disease were enrolled in this cross-sectional study. The subjects’ walking independence, physical characteristics, cognitive status, and blood test data were examined. Logistic regression analysis was performed, and cut-off values were calculated. RESULTS: The identified outcome measures and their respective cut-off values were as follows: the straight leg raising (SLR) repetition count, 27; the one-leg standing time (OLST), 3.6 s; and the orientation score of the mini-mental state examination (MMSE), 9/10. CONCLUSIONS: Our study findings suggest that the SLR repetition count, OLST, and the MMSE orientation score are simple outcome measures related to walking independence in inpatients with medical diseases in acute care hospitals.